Optimizing strategies in vendor-managed inventory scenarios - Felisia Miranti Sunarjo (2008)
The mathematical models of Pre VMI and VMI scenarios are developed and analysed. These models are developed to quantify the total cost of maintaining the inventory. Besides, the models are enhanced by considering the probabilistic demand, the service as well as the bullwhip effect.